A dictionary of atheism - Bullivant, Stephen; Lee, Lois ca. 20./21. Jh. (Oxford University Press, 2016)
This dictionary provides definitions of terms related to the subject of atheism, ranging from those of historic importance, including the history of the term 'atheist' itself, to crucial concepts in the contemporary study of atheism and related topics, such as nonreligion and postsecular.